1997
DOI: 10.1590/s0036-46651997000400001
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of adenovirus serotype 7 isolated in Brazil from acute respiratory disease patients during the period from 1980 to 1991

Abstract: Forty isolates of adenovirus type 7 were analized by restriction enzyme digestion with BamHI, SmaI, EcoRI and HindIII. These isolates were obtained from acute respiratory disease patients during the years 1980 to 1991. Only two genomic types were found: Ad7b and Ad7e, with Ad7b (87.5%) being more frequent than Ad7e (12.5%). The genomic type Ad7e appeared in the years 1980, 1981 and 1983. Ad7b appeared in 1982 and it was the only genomic type found from 1984 to 1991. Both genomic types were responsible for lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…Likewise, RSV was more frequently found in association with ARI in children older than 24 months (p=0.029) ( of the samples confirms the importance of this agent as frequent cause of ARI in children, particularly those older than 24 months 65.82%, (p=0.029), test significance. Although most studies conducted in temperate climates show RSV to be a frequent cause of ARI in children younger than 5, predominantly in infants, (Moraes et al 1997, Patwari et al 1996, Robertson et al 2004), the present study has revealed somewhat surprisingly that in this region of Brazil RSV was predominantly detected in children between 2 and 5 years of age.…”
Section: Duringcontrasting
confidence: 52%
“…Likewise, RSV was more frequently found in association with ARI in children older than 24 months (p=0.029) ( of the samples confirms the importance of this agent as frequent cause of ARI in children, particularly those older than 24 months 65.82%, (p=0.029), test significance. Although most studies conducted in temperate climates show RSV to be a frequent cause of ARI in children younger than 5, predominantly in infants, (Moraes et al 1997, Patwari et al 1996, Robertson et al 2004), the present study has revealed somewhat surprisingly that in this region of Brazil RSV was predominantly detected in children between 2 and 5 years of age.…”
Section: Duringcontrasting
confidence: 52%
“…Previous analysis of Ad7 in Brazil had identified only the genome types Ad7b and Ad7e (Wadell et al 1985, Moraes et al 1997, Kajon et al 1999. The analysis of 40 strains of Ad7 identified in cases of ARI in patients living in Southern and Southeastern regions of Brazil showed that in a period of 12 years (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991) only the genome types Ad7b and Ad7e were identified (Moraes et al 1997). Similar result was observed among 14 strains of Ad7 isolated from respiratory specimens from patients with ARI Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports of the genomic characterization of Brazilian Ad isolates from patients with respiratory, ocular and gastrointestinal infections have been published since 1988, but none of them included any Ad isolates of patients living in Northeast Brazil (Wadell et al 1985, Gomes et al 1988, Moraes et al 1997, Kajon et al 1999, de Albuquerque et al 2003, Moura et al 2007). These studies have shown an important genetic variability for members of subgenus C. Among members of subgenus B, serotype 3 has been represented by genotypes 3p1 and 3a variant described previously (Kajon et al 1999, Moura et al 2007.…”
mentioning
confidence: 99%
“…Information on the impact of adenovirus infections on the civilian adult population are rare as well, specially because the majority of epidemiologic studies that have been done in the country to evaluate the frequency of such infections were primarily targeted to the infantile population. In those studies the serotypes most common described were 1, 2, 3, 5 and 7 (TAKIMOTO et al, 1969;SUTMOLLER et al, 1983;NASCIMENTO et al, 1991;MORAES et al, 1997;KAJON et al, 1999).In this study, pharyngeal swabs were obtained from adults subjects: military recruits (221 specimens) from an army headquarter in Rio de Janeiro city, collected from April to November 2000, and civilian personnel (181 specimens), collected between March 2000 and November 2002, also in Rio de Janeiro city. The samples were collected from subjects with or without clinical symptoms.…”
mentioning
confidence: 98%